PTU-054 In children with eosinophilic oesophagitis, symptom resolution does not correspond with endoscopic or histological improvement. (June 2019) - Rao, Arati; Alrusayni, Yasir; Vadamalayan, Babu; Thangarajah, Dhamyanthi; Deheragoda, Maesha; Hope, Ben
Abstract : Introduction: Eosinophilic esophagitis (EoE) is a chronic, local immune-mediated condition characterised by symptoms relating to oesophageal dysfunction and histologically by eosinophil-predominant inflammation. In this study, we describe symptomatic, endoscopic and histological response to treatment in children attending a tertiary paediatric gastroenterology centre. Methods: Retrospective analysis of all children (age <18 yrs) diagnosed with EoE from 1/1/12 to 6/1/17 with ≥ 1 year follow-up. Diagnosis was based on the presence of ≥15 eosinophils/high powered field (eos/hpf) in endoscopic oesophageal biopsies. Children with mucosal eosinophilia elsewhere in the gut were excluded. Histological review was carried out by an independent pathologist. Data was analysed using SPSS 21 (Armonk, New York, NY, USA) and Prism 7 (San Diego, CA, USA). Significance was two-tailed and defined as p<0.05. Results: Of the 25 children who met the criteria, the mean age at diagnosis was 5.8 yrs with a mean symptom duration of 16.4 months, and a mean eos/hpf count of 26.3. The commonest presenting symptoms were vomiting and abdominal pain. All patients received a PPI; 22 were prescribed dietary therapy; and 16 topical steroids. There was a high rate of symptomatic improvement, with 18 patients denying any gut symptoms at latest follow-up. However, even within this group a significant fall in eos/hpf count between diagnosis and follow up endoscopies was not observed (figure 1). This was seen regardless of the treatment modality used: dietary manipulation before and after mean [SD] 26.9 [15.1] vs 23.9 [20.0], p=0.4; topical steroids mean [SD] 31.4 [14.1] vs 28 [19.1], p=0.5; both concurrently mean [SD] 32.8 [14.4] vs 30.2 [19.7], p=0.7. Overall, 17/25 (68%) still had an eos/hpf count of >15. Only 20% had macroscopically and histologically normal mucosa at follow up endoscopy. None of the children had a stricture at diagnosis or developed one during follow up. Conclusions: Despite a high rate of symptom improvement, in only a small minority did the eos/hpf count fall below the diagnostic level. Normalisation of endoscopic appearance was also less common that has been reported. It has been proposed that persistent eosinophilia leads to fibrotic tissue remodelling and disease progression. Longer term studies with larger cohorts are needed to confirm this hypothesis. Until then it will remain unclear whether more aggressive intervention is indicated in asymptomatic patients.